Salud mental universitaria Salud mental universitaria: voces, trayectorias y prácticas situadas - Abarzúa Cubillos, Marianella (Social-ediciones, 2022)
Mental health condenses and questions not only conditions related to the field of health but also corresponds to the subjective translation of social, political, and economic conditions with which it is linked. The chilean social upheaval, feminist revolt, and currently the pandemic have revealed pre-existing social fractures, inequities, and exclusions. Similarly, mental health as a psychosocial issue demands approaches that integrate social life with the singularities of subjective experience. This book is the result of a research process on mental health in the context of university life and includes interdisciplinary and multisectoral approaches in an effort to address the issue in its complexity. The biographical and subjective trajectories of students at the University of Chile are joined by the voices of actors and actresses who, from their institutional and professional roles, provide an account of a multiple and diverse reality, as well as the need to collectively address a problem that concerns everyone. Hence, the relevance of recognizing and complementing, through the contribution of the Social Sciences and situated experiences, the possibility of thinking differently (innovation) about a problem often co-opted by exclusively epidemiological perspectives. Because it is rather about recognizing in the approach to student mental health a political demand - and an opportunity - at both the level of specific preventive and therapeutic practices, and within the framework of institutional and community-based plans and programs to be implemented.